Evaluation of investment in works by tax and its socio-economic impact in the Tacna region, period 2009 - 2016 - Bendezú Meléndez, Nataly Jennifer (2020)
Objective: To determine the relation of the investment in works by taxand the socioeconomic impact in the Region of Tacna, Period 2009 - 2016. Methodology: A correlational - quantitative design was used, using the documentary review of the Ministry of Economy and Finance, ProInversión, Obras por Impuesto, as well as a structured questionnaire, applied to the beneficiary population of works for Tax in the Region of Tacna. Results: The relation between the investment in works by tax and the socio-economic impact in the Region of Tacna is significant. Likewise, the investment in works for tax from 2009 to 2016 was moderate, as far as the socio-economic impact between 2009 and 2016 was favorable. Finally it was verified that the investment in works by tax in the Region of Tacna, improved its growth from the year 2014. Conclusion: the relationship between investment in works by tax and socioeconomic impact in the Region of Tacna, Period 2009 - 2016 if significant. Since the statistical analysis of both variables shows that the works by tax have a direct impact on the socio-economic impact in the Region of Tacna